Aflatoxin and fumonisin contamination of cassava products and maize grain from markets in Tanzania and republic of the Congo - Manjula, K.; Hell, K.; Fandohan, P.; Abass, A.; Bandyopadhyay, Ranajit (Informa UK Limited, 2009)
Food safety and compliance with international standards is a major challenging to achieve food security in sub-Saharan Africa. The present study evaluated the occurrence of Aspergillus flavus, Fusarium spp., and related fungi, and resultant aflatoxins and fumonsins in dried cassava and maize samples from various markets and villages in Tanzania and Congo. The relationship between mycotoxins and length of storage period was also elucidated. The levels of aflatoxin B1varied from 0.3 to 4.4ppb in cassava chips and flour, and from 0.1 to 13.0ppb in stored cassava samples, with relatively high levels of contamination found in cassava stored for 4 months. Maize kernels showed high aflatoxin concentrations, with means ranging from 0.04 to 120ppb. On maize, the dominant mycoflora were Aspergillus spp. (3.3%–39.5%) and Fusarium spp. (42%–70.5%), potentially causing serious health risks to consumers of these products. Low levels of fumonisin ranging from 0 to 0.07ppm were found in cassava chips and flour with mean values ranging from 0.001 to 0.006ppm. Maize recorded relatively higher fumonisin levels ranging from 0.02 to 9.4ppm, indicating that maize is potentially a more serious risk to consumer health than cassava. This needs to be taken into account when developing strategies to reduce toxin contamination and improve health of populations. Aflatoxin in maize is a chronic problem in the two countries surveyed, limiting marketability and income. Nevertheless the collected cassava samples are also prone to aflatoxin contamination, but not fumonisin contamination.